2023
DOI: 10.1097/tp.0000000000004396
|View full text |Cite
|
Sign up to set email alerts
|

Relating Molecular T Cell–mediated Rejection Activity in Kidney Transplant Biopsies to Time and to Histologic Tubulitis and Atrophy-fibrosis

Abstract: Background. We studied the variation in molecular T cell–mediated rejection (TCMR) activity in kidney transplant indication biopsies and its relationship with histologic lesions (particularly tubulitis and atrophy-fibrosis) and time posttransplant. Methods. We examined 175 kidney transplant biopsies with molecular TCMR as defined by archetypal analysis in the INTERCOMEX study ( ClinicalTrials.gov #NCT01299168). TCMR activity was defined by a molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…122,123 Banff 2017 revised this classification. 121–124 We recently confirmed that tubulitis is a robust feature of TCMR even in late biopsies with atrophy-fibrosis, 108 but the atrophy-fibrosis can make it difficult to score tubulitis.…”
Section: The Genome Canada MMDX Project: Defining Rejection and Injur...mentioning
confidence: 84%
See 1 more Smart Citation
“…122,123 Banff 2017 revised this classification. 121–124 We recently confirmed that tubulitis is a robust feature of TCMR even in late biopsies with atrophy-fibrosis, 108 but the atrophy-fibrosis can make it difficult to score tubulitis.…”
Section: The Genome Canada MMDX Project: Defining Rejection and Injur...mentioning
confidence: 84%
“…FIGURE 15. Various relationships between molecular, histological, and clinical variables and graft survival postbiopsy 108,114. (A) Survival shown per archetype group in 1679 biopsies.…”
mentioning
confidence: 99%
“…Some TCMR2 biopsies had low dd-cfDNA, possibly because TCMR2 is less intense and has more fibrosis than TCMR1. 27 Among injury archetype groupings, 28,29 dd-cfDNA was highest in molecular AKI (mAKI; P < 0.0001; Figure 3C). Removing biopsies diagnosed as rejection from the injury archetype set resulted in lower dd-cfDNA in all groups.…”
Section: Estimated Dd-cfdna In MMDX and Molecular Rejection And Injur...mentioning
confidence: 96%
“…Biopsies were diagnosed by their MMDx signouts and automated archetypal assignments of rejection and injury. 17,[23][24][25][26][27][28][29] Biopsies with no molecular rejection taken within 6-wk posttransplant were classified as no-rejection-clinical AKI (cAKI), and the remaining NR biopsies were classified as Normal. A group of "pristine" biopsies was classified as NRNI based on intersection of MMDx Normal and archetypal no injury in the whole population (SDC, http://links.lww.com/TP/C935).…”
Section: Molecular Diagnoses Of Rejection and Injurymentioning
confidence: 99%
See 1 more Smart Citation